2021
DOI: 10.1177/00336882211018499
|View full text |Cite
|
Sign up to set email alerts
|

Glocalizing ELT Reform in China: A Perspective from the Use of English in the Workplace

Abstract: With the largest number of English learners in the world, the influence of the English language teaching (ELT) reform in China cannot be underestimated. This article explores the implications of the actual use of English in China’s workplace for ELT reform in the context of English as a lingua franca (ELF). On the basis of cross-validated data (questionnaire survey and focused interview) collected from 2495 participants, we argue that ELT reform in China should be geared towards using English communicatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The technological products of artificial intelligence and 5G are bound to bring about changes in the college English teaching model. With the improvement of the online teaching model, teachers will have a difficult time collecting, analyzing, and processing bid data as online education and their efficiency will suffer [ 1 ]. Artificial intelligence and 5G, on the other hand, can address these challenges in a systematic and time-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…The technological products of artificial intelligence and 5G are bound to bring about changes in the college English teaching model. With the improvement of the online teaching model, teachers will have a difficult time collecting, analyzing, and processing bid data as online education and their efficiency will suffer [ 1 ]. Artificial intelligence and 5G, on the other hand, can address these challenges in a systematic and time-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…This, in our opinion, can possibly be attributed to the relatively easy access to the data by analyzing English MOOCs on iCourse. As China boasts the largest number of English learners in the world (He and Li, 2021) and iCourse is the largest MOOC platform in China (Wu and Chen, 2021), the choice of an overwhelming number of English MOOCs from iCourse would make data collection more easily accessible and feasible. However, this lack of data diversity could affect its reliability, as data heterogeneity is integral to the validity of analysis (Pitard, 2019).…”
Section: Data Collectionmentioning
confidence: 99%
“…These findings are consistent with research also in the professional world. He and Li (2023) note that the Chinese EFL curriculum focuses heavily on grammatical accuracy and the native-speaker standard. Questionnaire data with professionals in various contexts indicated that such programs do not reflect real uses for English in the Chinese professional world; a more glocalized approach would include communication-focused methods, with the student at the center of learning experience.…”
Section: Introductionmentioning
confidence: 99%